Rhythm Generation and Rhythm Perception in Insects: The Evolution of Synchronous Choruses - Hartbauer, Manfred; Römer, Heiner (Frontiers in Neuroscience, 2016)
Insect sounds dominate the acoustic environment in many natural habitats such as rainforests or meadows on a warm summer day. Among acoustic insects, usually males are the calling sex; they generate signals that transmit information about the species-identity, sex, location or even sender quality to conspecific receivers. Males of some insect species generate signals at distinct time intervals, and other males adjust their own rhythm relative to that of their conspecific neighbors, which leads to fascinating acoustic group displays. Although signal timing in a chorus can have important consequences for the calling energetics, reproductive success and predation risk of individuals, still little is known about the selective forces that favor the evolution of insect choruses. Here, we review recent advances in our understanding of the neuronal network responsible for acoustic pattern generation of a signaler, and pattern recognition in receivers. We also describe different proximate mechanisms that facilitate the synchronous generation of signals in a chorus and provide examples of suggested hypotheses to explain the evolution of chorus synchrony in insects. Some hypotheses are related to sexual selection and inter-male cooperation or competition, whereas others refer to the selection pressure exerted by natural predators. In this article, we summarize the results of studies that address chorus synchrony in the tropical katydid Mecopoda elongata, where some males persistently signal as followers although this reduces their mating success.